RELEVANSI PERDA NOMOR 3 TAHUN 1991 DALAM PEMBANGUNAN PARIW ISATA BUDAYA BALI - Hadi Sukarno, Teguh (JURNAL KEPARIWISATAAN, 2007)
The Government of Bali decided that culture tourism concepts were viewed as the ideology, spirit, guidelines, framework and solutions in developing tourism in Bali. These decisions were then legitimized in a form of provincial rules "Perda no 3, tahun 1974" concerning the cultural tourism. The relationship of tourism development and cultural development runs in harmony. It can be seen obviously that the Balinese awareness of their culture comes simultaneously as the tourism of Bali develops. The culture of Bali which is based on Hindu Relegion is implemented as a fundamental base, dominant factor and motor by which the tourism of Bali is developed.